A fast, always positive definite and normalizable approximation of non-Gaussian likelihoods - Sellentin, Elena (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. In this paper we extend the previously published dali-approximation for likelihoods to cases in which the parameter dependence is in the covariance m
Gesehen am 16.06.2020